Environmental exposure to perchlorate, nitrate, and thiocyanate in relation to chronic kidney disease in the general US population, NHANES 2005–2016 - Wei Li; Hong Wu; Xuewen Xu; Yange Zhang; Jinjiao Li; Yuanyuan Ji (Chinese Medical Journal, 2023)
Abstract. Background:. Few studies have explored the impact of perchlorate, nitrate, and thiocyanate (PNT) on kidney function. This study aimed to evaluate the association of urinary levels of PNT with renal function as well as the prevalence of chronic kidney disease (CKD) among the general population in the United States. Methods:. This analysis included data from 13,373 adults (≥20 years) from the National Health and Nutrition Examination Survey 2005 to 2016. We used multivariable linear and logistic regression, to explore the associations of urinary PNT with kidney function. Restricted cubic splines were used to assess the potentially non-linear relationships between PNT exposure and outcomes. Results:. After traditional creatinine adjustment, perchlorate (P-traditional) was positively associated with estimated glomerular filtration rate (eGFR) (adjusted β: 2.75; 95% confidence interval [CI]: 2.25 to 3.26; P < 0.001), and negatively associated with urinary albumin-to-creatinine ratio (ACR) (adjusted β: −0.05; 95% CI: −0.07 to −0.02; P = 0.001) in adjusted models. After both traditional and covariate-adjusted creatinine adjustment, urinary nitrate and thiocyanate were positively associated with eGFR (all P values <0.05), and negatively associated with ACR (all P values <0.05); higher nitrate or thiocyanate was associated with a lower risk of CKD (all P values <0.001). Moreover, there were L-shaped non-linear associations between nitrate, thiocyanate, and outcomes. In the adjusted models, for quartiles of PNT, statistically significant dose–response associations were observed in most relationships. Most results were consistent in the stratified and sensitivity analyses. Conclusions:. Exposures to PNT might be associated with kidney function, indicating a potential beneficial effect of environmental PNT exposure (especially nitrate and thiocyanate) on the human kidney.